2022
DOI: 10.1093/cercor/bhac400
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in brain aging: heterogeneity in cortico-hippocampal but not caudate atrophy rates

Abstract: It is well documented that some brain regions, such as association cortices, caudate, and hippocampus, are particularly prone to age-related atrophy, but it has been hypothesized that there are individual differences in atrophy profiles. Here, we document heterogeneity in regional-atrophy patterns using latent-profile analysis of 1,482 longitudinal magnetic resonance imaging observations. The results supported a 2-group solution reflecting differences in atrophy rates in cortical regions and hippocampus along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3
2

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Using hippocampus as test-region, there was a significant main effect of scanner on volume (F = 4.13, p = 0.046), but the between-participant rank order was close perfectly retained between scanners, with a mean between-scanner Pearson correlation of r = 0.98 (range 0.94-1.00). Similar analyses of cortical regions also revealed close correspondence across scanners (Nyberg et al, 2023). Thus, including site as a random effect covariate in the analyses of hippocampal volume is likely sufficient to remove the influence of scanner differences.…”
Section: Magnetic Resonance Imaging Acquisition and Analysismentioning
confidence: 59%
“…Using hippocampus as test-region, there was a significant main effect of scanner on volume (F = 4.13, p = 0.046), but the between-participant rank order was close perfectly retained between scanners, with a mean between-scanner Pearson correlation of r = 0.98 (range 0.94-1.00). Similar analyses of cortical regions also revealed close correspondence across scanners (Nyberg et al, 2023). Thus, including site as a random effect covariate in the analyses of hippocampal volume is likely sufficient to remove the influence of scanner differences.…”
Section: Magnetic Resonance Imaging Acquisition and Analysismentioning
confidence: 59%
“…Using hippocampus as test-region, there was a significant main effect of scanner on volume (F = 4.13, p = .046), but the between-participant rank order was close perfectly retained between scanners, with a mean between-scanner Pearson correlation of r = .98 (range .94-1.00). Similar analyses of cortical regions also revealed close correspondence across scanners (Nyberg et al 2022). Thus, including site as a random effect covariate in the analyses of hippocampal volume is likely sufficient to remove the influence of scanner differences.…”
Section: Methodsmentioning
confidence: 63%
“…While the adaptive stress response is important for survival, repeated hormone adaption to stress activation of the hypothalamus-pituitary-adrenal (HPA) axis results in lasting structural and functional disturbances of the limbic lobe [47,48,49]. Further, a recent study with longitudinal MRI data showed that aging is characterized more by hippocampal atrophy than by cortical thickness [50]. These ndings together with our results, suggest the burden of SES disadvantage may be more likely to exaggerate towards the limbic lobe with age.…”
Section: Discussionmentioning
confidence: 99%